Challenges to multilateral disarmament: Global perspectives on UN disarmament, arms control and non-proliferation - Trine Rosengren Pejstrup (Danish Institute for International Studies (DIIS), 2024)
The complexities of multipolarity, heightened global tensions, and increasing militarisation are reshaping the disarmament, arms control and non-proliferation landscape within the United Nations. This report examines these evolving dynamics, contextualising their historical importance and assessing the impact of shifting geopolitical forces and technological advances on disarmament and arms control. Building on data collection focused on multilateral disarmament, it confirms two critical trends in the UN system: a significant trust deficit between member states and declining confidence in multilateral disarmament institutions, both of which severely undermine disarmament efforts. While these two trends are well-established, this report showcases how these are evident in multilateral disarmament. From a disarmament perspective, distrust goes beyond mere compliance and extends to a trust deficit in the design and intent behind disarmament, arms control and non-proliferation agreements while a lack of confidence is apparent in discussions around the challenges and opportunities posed by new technologies as well as a turn to soft law rather than hard law. The report provides recommendations for Danish diplomats as Denmark prepares for a non-permanent seat on the Security Council for 2025-2026. It advocates for an integrated approach that aligns disarmament and arms control with broader efforts to promote global peace and security.
Keywords: 300; multilateral disarmament; UN; arms control; disarmament; non-proliferation